Understanding the Stability of Passenger Vehicles Exposed to Water Flows through 3D CFD Modelling - Ebrahim Hamid Hussein Al-Qadami, Ebrahim Hamid Hussein Al-Qadami; Mohd Adib Mohammad Razi, Mohd Adib Mohammad Razi; Wawan Septiawan Damanik, Wawan Septiawan Damanik; Mustaffa, Zahiraniza; Eduardo Martinez-Gomariz, Eduardo Martinez-Gomariz (Mdpi, 2023)
A vehicle exposed to flooding may lose its stability and wash away resulting in potential injuries and fatalities. Traffic disruption, infrastructure damage, and economic losses are also additional effects of the washed vehicles. Therefore, understanding the responses of passenger vehicles during flood events is of the utmost importance to reduce flood risks and develop accurate safety guidelines. Previously, flooded vehicle stability was investigated experimentally, theoretically, and numerically. However, numerical investigations are insufficient, of which only a few studies have been published since 1967. Furthermore, coupled motion simulations have not been employed to investigate the hydrodynamic forces on flooded vehicles. In this paper, a numerical framework was proposed to assess the response of a full-scale medium-size passenger vehicle exposed to floodwaters through three-dimensional computational fluid dynamic modelling. The vehicle was simulated under subcritical and supercritical flows with the Froude number ranging between 0.09 and 2.46. The results showed that the vehicle experienced the floating instability mode once the flow depth reached 0.38 m, while the sliding instability mode was observed once the depth × velocity threshold function exceeded 0.36 m2/s. In terms of hydrodynamic forces, it was noticed that the drag force decreased with the increment of the Froude number and flow velocity. On the other hand, the fraction and buoyancy forces are mainly governed by the flow depth at the vehicle vicinity. The drag coefficient was noticed to be less than 1 for supercritical flows and more than 1 for subcritical flows. The numerical results obtained through the framework introduced in this study demonstrate favorable agreement with three different previously published experimental outcomes.